Economic Preferences of Medicinal Plants and Chemical Medicines by Communities in the Working Area of Dolago Tanggunung Forest Management Unit - Gaibu, Jein Trivena; Umar, Syukur; Pribadi, Hendra; Anwar, Anwar; Rachman, Imran; Hamzari, Hamzari (PT Inovasi Pratama Internasional, 2025)
This research investigates the economic patterns of expenditure and preferences regarding medicinal plants and chemical drugs by people living around the forest in the working area of ​​the Dolago Tanggunung Forest Management Unit. This research aims to analyze people's economic preferences in the use of medicinal plants and chemical drugs by identifying the types of medicinal plants used, their economic value, and comparison of expenditure between the two types of drugs. This research used the Stratified Random Sampling method with 100 respondents, and data analysis was carried out using the paired t-test and multiple linear regression with the t test to measure the influence of various factors on the frequency of use of medicinal plants. The results of the research show that there are 60 types of medicinal plants from 35 families that are used by the local community. The effectiveness factor (β=0.30, p=0.003) has the strongest influence on the frequency of use of medicinal plants, followed by reasons for use (β=0.15, p=0.035) and the price of chemical drugs (β=-0.25, p=0.007). The high price of chemical drugs encourages people to turn to medicinal plants as an alternative. On the other hand, the level of trust in medicinal plants (p=0.215) did not have a significant effect on the frequency of use. Thus, economic and effectiveness factors are more dominant in determining people's preferences for medicinal plants compared to trust factors. Integration between traditional and modern medicine can be a solution to improve public health in a sustainable manner.